Highly efficient all-inorganic perovskite solar cells with suppressed non-radiative recombination by a Lewis base - Jing Wang (Nature Portfolio, 2020)
There has been a hot competition to optimize the device performance for all-inorganic perovskite solar cells. Here Wang et al. employ a Lewis base molecule to suppresses the non-radiative recombination in the inverted device and achieve a champion efficiency of 16.1%.